2017
DOI: 10.1155/2017/9194261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extremely Low-Frequency Electromagnetic Fields on Neurogenesis and Cognitive Behavior in an Experimental Model of Hippocampal Injury

Abstract: Exposure to extremely low-frequency electromagnetic fields may induce constant modulation in neuronal plasticity. In recent years, tremendous efforts have been made to design a suitable strategy for enhancing adult neurogenesis, which seems to be deterred due to brain senescence and several neurodegenerative diseases. In this study, we evaluated the effects of ELF-EMF on neurogenesis and memory, following treatment with trimethyltin chloride (TMT) as a neurotoxicant. The mice in all groups (n = 56) were inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…Regarding the impact of ELF‐EMF, the results of our study are in conflict with studies that report the neurogenesis effects of ELF‐EMF (Cuccurazzu et al., 2010 ; Gao et al., 2021 ; Podda et al., 2014 ; Sakhaie et al., 2017b ). To our knowledge, there is no study on the effects of prenatal ELF‐EMF on anxiety‐like behavior until now, and this is the first time that neurodegenerative effects of ELF‐EMF in the hippocampus and PFC are reported.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact of ELF‐EMF, the results of our study are in conflict with studies that report the neurogenesis effects of ELF‐EMF (Cuccurazzu et al., 2010 ; Gao et al., 2021 ; Podda et al., 2014 ; Sakhaie et al., 2017b ). To our knowledge, there is no study on the effects of prenatal ELF‐EMF on anxiety‐like behavior until now, and this is the first time that neurodegenerative effects of ELF‐EMF in the hippocampus and PFC are reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, anti-stress effect of ELF-EMF has been reported (Nafisi et al, 2009). Besides, neuroregenerative effects of ELF-EMF in hippocampus were reported by several studies Sakhaie et al, 2017a;Tasset et al, 2012). Furthermore, ELF-EMF has been found to increase neuroplasticity (Cichon et al, 2020;.…”
Section: Introductionmentioning
confidence: 90%
“…Studies on the rat traumatic brain injury model [ 110 ] and on rat Alzheimer’s disease model [ 49 ] have shown that ELF-MF reversed pathological brain damages and learning and memory abilities impairment. Similar effects were obtained after exposure of neurotoxin-injected mice to ELF-MF (50 Hz, 1 mT); the deficits such as neuronal maturation impairment, neurogenesis decrease, and memory disturbance decreased [ 111 ]. Studies on the beneficial effects of ELF-MF might yield fruitful insights related to clinical therapy of nervous-system-related diseases.…”
Section: Molecular Stress Response To Elf-mfmentioning
confidence: 59%
“…The activation of cellular responses and repairing systems, mediated by REMFS-induced HSF1, could represent an important approach for managing Alzheimer and other age-related diseases (Perez et al 2019, Perez et al 2008b. Within this context, the exposure to electromagnetic fields induce a constant modulation of neural system, improving learning and memory impairment by stimulating neurogenesis in mice (Sakhaie et al 2017, Leone et al 2014, and implementing the achievement of a neurogenic phenotype in PC12 cell dopaminergic model (Maioli et al 2015). When exposed to REAC technology, human adipose-derived stem cells (ADSCs) exposed to prolonged culturing senescence, showed a significant downregulation in the expression of senescence-associated genes (p16INK4, p53, p19) and β-galactosidase (Maioli et al 2014a.…”
Section: Cytoskeleton and Membranesmentioning
confidence: 99%